Upper Campanian–Maastrichtian chronostratigraphy of the Skælskør‐1 core, Denmark: correlation at the basinal and global scale and implications for changes in sea‐surface temperatures. (6th March 2015) - Thibault, Nicolas; Anderskouv, Kresten; Bjerager, Morten; Boldreel, Lars O.; Jelby, Mads E.; Stemmerik, Lars; Surlyk, Finn
<x xml:space="preserve">Abstract</x> The lithostratigraphy, calcareous nannofossil biostratigraphy, carbon‐ and oxygen‐isotope stratigraphy and gamma‐ray profile are presented for the Skælskør‐1 core, eastern Denmark. The correlation of carbon isotopes to Gubbio (Italy) and ODP Site 762C (Indian Ocean) provides the chronostratigrahical framework of the core through a tie to magnetostratigraphy. Two new carbon‐isotope excursions are defined for the uppermost Maastrichtian of the core and prove useful for long‐distance correlation. Twenty stratigraphic tie‐points are used for correlation of the upper Campanian–Maastrichtian interval by combining carbon‐isotope and gamma‐ray variations. Significant dissimilarities in the gamma‐ray profiles of the Danish Basin cores preclude the sole use of this tool for basin‐scale correlations. Bulk oxygen‐isotopes and semi‐quantitative abundance changes in the warm‐water calcareous nannofossil Watznaueria barnesiae and the cool‐water Kamptnerius magnificus highlight the following past changes in sea‐surface temperatures (SSTs): relatively warm late Campanian SSTs, cooling across the Campanian–Maastrichtian boundary and through the early Maastrichtian, warming across the early–late Maastrichtian transition, cooling in the late Maastrichtian, intense warming in the latest Maastrichtian chron C29r, followed by a very short episode of cooling immediately before the Cretaceous–Palaeogene boundary. The late Campanian–Maastrichtian evolution in sea water temperatures inferred from the Danish Basin is similar to that delineated at tropical latitude oceanic sites.